2009
DOI: 10.1007/bf03346565
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polyphenol-containing antioxidants on oxidative stress and lipid peroxidation in Type 2 diabetes mellitus without complications

Abstract: These observations indicated that the polyphenol-rich antioxidant supplement containing pomegranate extract, green tea extract, and ascorbic acid has important antagonizing effects on oxidative stress and lipid peroxidation in patients with Type 2 DM and might be beneficial in preventing cardiovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 22 publications
7
71
0
Order By: Relevance
“…All other chemicals used were of analytical grade. "moderate correlation"; 0.60-0.79 "strong correlation"; 0.80-1.0 "very strong correlation", as mentioned in other research studies (Fenercioglu et al, 2010;Floegela et al, 2011;Harris et al, 2011).…”
Section: Reagentssupporting
confidence: 51%
“…All other chemicals used were of analytical grade. "moderate correlation"; 0.60-0.79 "strong correlation"; 0.80-1.0 "very strong correlation", as mentioned in other research studies (Fenercioglu et al, 2010;Floegela et al, 2011;Harris et al, 2011).…”
Section: Reagentssupporting
confidence: 51%
“…A possible mechanism of decreasing oxidative damage in cells by garlic extracts is by preventing lipid peroxidation (Fenercioglu et al, 2010). In the present study, the extracts demonstrated a high antioxidant activity against hydrolytic rancidity of crude palm oil in a concentration dependent manner.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, development of targeted therapeutics is needed in order to ameliorate or eliminate diabetes associated kidney damage. In both experimental and clinical models of diabetes, antioxidants have been reported to reduce markers of oxidative stress [12,13]. Besides, some studies have showed that antioxidants are effective and cheaper than conventional therapy in management of some diseases [14].…”
Section: Introductionmentioning
confidence: 99%